OBSERVING PEOPLE'S REACTIONS AND RESPONSES TO URBAN ROAD TRAFFIC NOISE (RTN) IN JORDAN - Jadaan, Khair; Alsarayreh, Duha; Obaid , Mohammed (Journal of Civil Engineering, Science and Technology, 2021)
The subjective aspect of assessing Road Traffic Noise (RTN) in urban agglomerations is crucial, as it takes into consideration the sensitivity and specific reactions of residents to Road Traffic noise (RTN) in their living environments. This paper aims to present a detailed sociological study initiated to measure the level of public awareness regarding RTN and estimate the impact of RTN disturbance on RTN disturbance their daily activities. For this purpose, an attitudinal survey was conducted using a predesigned questionnaire with limited noise measurements. The questioners were distributed to the neighboring residents of one of the most congested arterial roads in Amman, Jordan’s capital. The questioner firstly focused on evaluating the awareness of respondents of the problem magnitude and its environmental and health impacts, and secondly, assessing the effects of RTN as perceived by the respondents on different daily activities. The analysis of the collected data found that around 50% of respondents believe that RTN impacts the environment, and 60% believe that RTN affects human health, while 38% consider changing their place of residence and moving to a quieter place. The main results of the study showed that RTN causes annoyance to people while performing their daily activities, especially while studying and resting. Further main reported impacts included causing fatigue (64%), anxiety (75%), nervousness (87%), focus reduction (89%), and discomfort (90%).